Diversity analysis of Lasiodiplodia theobromae inciting root and collar rot of Jatropha curcas using molecular tools - RAVINDRANATH K. PATIL, HEMANT N. PRAJAPATI* and (Indian Phytopathology, 2015)
Jatropha (Jatropha curcas L.) plantation is threatened by root rot and collar rot caused by Lasiodiplodia theobromae Pat. (Griffon & Maubl). Nine isolates of Lasiodiplodia theobromae collected from jatropha from various regions in Gujarat and Madhya Pradesh were characterized using molecular tools. Dendrogram generated by using the 14 RAPD loci formed two clusters. The highest similarity index value of 0.50 was found between Lt-5 isolate and Lt-6 isolate. The average similarity coefficient among isolates was 0.403. The data obtained from Random Amplification of Polymorphic DNA (RAPD) with 14 arbitrary primers produced 279 loci and 861 amplicons. Out of the 279 loci produced, 266 were polymorphic and hence the total polymorphism was found to be 95.60%. Average number of amplicons per primer was found to be 19.9 and average number of polymorphic loci obtained per primer (Assay Efficiency Index) was found to be 19. Out of 14 primer, 5 successfully produced 100% polymorphism.